Typologia reżimów hybrydalnych. Ujęcie teoretyczno-metodologiczne - Prokop, Maryana (Historia i Polityka, 2017)
In the article the author raises the issues of theoretical and methodological aspects of research studies on hybrid regimes being a combination of democracy and authoritarianism. The aim of the research was to present and develop a typology of hybrid regimes. The implementation consisted of two stages. At the first stage the operationalisation of category of typology was developed and the structure schema of its construction was planned. At the second stage the planned structure schema of typology construction was applied in the creation to typology of hybrid regimes.